The Jewish Family in Antiquity - Satlow, Michael L.; Cohen, Shaye J. D. (Book collections on Project MUSE., 2020)
This volume consists of papers (or the offspring of papers) that were delivered by the Hellenistic Judaism section of the 1990 and 1991 annual meetings of the Society for Biblical Literature. In recognition of the fact that so little work had been down on the subject, presenters were not asked to focus on a single set of questions, a single body of evidence, or utilize a single methodology. Rather the goal was to get a sense of the range of possibilities suggested by the topic. The variety in this collection mirrors the variety of our evidence and the variety of questions that can be asked of it.